PENGUATAN KEMAMPUAN MEMBACA SISWA SEKOLAH DASAR MELALUI PROGRAM REHAT LITERASI PADA KEGIATAN PMDS - Bayu, Muhammad; Nurhabibah, Prabawati; Permatasari, Deti; A'irin, Marshanda; Cahyana, Defania Sinda; Alfinafillah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading ability is one of the fundamental skills that must be mastered by elementary school students because it supports the learning process in various subjects. However, some students still experience difficulties in reading fluently, which can affect their academic development. This study aims to describe the implementation of the Rehat Literasi program in strengthening the reading ability of elementary school students at SDN 1 Weru Lor through the Pengabdian Mahasiswa di Sekolah (PMdS) program of Universitas Muhammadiyah Cirebon. The research used a descriptive qualitative approach with observation, documentation, and interviews as data collection techniques. The program was implemented from September 29 to December 1, 2025, involving students from grades I to VI who had not yet achieved reading fluency. Activities were conducted in the school library after class hours through guided reading assistance according to students’ reading levels. In addition, the Bintang Literasi program was implemented as a reward system to motivate students to participate actively in reading activities. The results show that the Rehat Literasi program contributed to improving students’ reading fluency and increasing their interest in reading. Students became more confident in reading and were more enthusiastic about participating in literacy activities. Therefore, the Rehat Literasi program can serve as an effective strategy to support the strengthening of basic literacy skills among elementary school students.